Kesehatan Sosial-Emosional, Persepsi terhadap Iklim Sekolah, dan Psychological Sense of School Membership Siswa Sekolah Dasar - Widiasmara, Nur; Ambarsari, Ranti; Faried, Elan Zacky (JURNAL PSIKOLOGI INSIGHT, 2021)
This study aimed to know how psychological sense of school membership mediate the effect of perception of iklim sekolahon kesehatan sosial-emosional among elementary school students. The participants were 132 grades 4–6 students in Sleman and Yogyakarta. The instruments were the Social Emotional Health Survey-Primary School Scale (Furlong et al., 2013), The Psychological sense of school membership (PSSM) Scale (Goodenow, 1993), and the Iklim sekolahSurvey: Elementary (La Salle, et al., 2016). PROCESS analysis was employed to test for mediation. The results indicated that there is an influence of iklim sekolahon kesehatan social-emosional mediated by the psychological sense of school membership in elementary school students in Sleman and Yogyakarta.Penelitian ini bertujuan untuk mengetahui bagaimana peran mediasi psychological sense of school membership dalam pengaruh iklim sekolah terhadap kesehatan sosial-emosional pada siswa sekolah dasar di Sleman dan Yogyakarta. Partisipan penelitian ini adalah 132 siswa kelas 4–6. Instrumen yang digunakan adalah Social Emotional Health Survey-Primary School Scale (Furlong dkk., 2013), The Psychological sense of school membership (PSSM) Scale (Goodenow, 1993), dan School Climate Survey: Elementary (La Salle, dkk., 2016). Analisis PROCESS digunakan untuk menguji mediasi. Hasilnya menunjukkan bahwa ada pengaruh iklim sekolah dan kesehatan sosial-emosional yang dimediasi psychological sense of school membership pada siswa SD di Sleman dan Yogyakarta.